The tryptophan-derived endogenous arylhydrocarbon receptor ligand 6-formylindolo[3,2-b]carbazole (FICZ) is a nanomolar UVA-photosensitizer in epidermal keratinocytes - Park, Sophia L. (J Invest Dermatol, 2014)
Endogenous UVA-chromophores may act as sensitizers of oxidative stress underlying cutaneous photoaging and photocarcinogenesis, but the molecular identity of non-DNA key chromophores displaying UVA-driven photodyamic activity in human skin remains largely undefined. Here we report that 6-formylindolo[3,2-b]carbazole (FICZ), a tryptophan photoproduct and endogenous high affinity aryl hydrocarbon receptor (AhR) agonist, acts as a nanomolar photosensitizer potentiating UVA-induced oxidative stress irrespective of AhR ligand activity. In human HaCaT and primary epidermal keratinocytes, photodynamic induction of apoptosis was elicited by the combined action of solar simulated UVA and FICZ, whereas exposure to the isolated action of UVA or FICZ did not impair viability. In a human epidermal tissue reconstruct, FICZ/UVA-cotreatment caused pronounced phototoxicity inducing keratinocyte cell death, and FICZ photodynamic activity was also substantiated in a murine skin exposure model. Array analysis revealed pronounced potentiation of cellular heat shock, ER stress, and oxidative stress response gene expression observed only upon FICZ/UVA-cotreatment. FICZ photosensitization caused intracellular oxidative stress, and comet analysis revealed introduction of formamidopyrimidine-DNA glycosylase (FPG)-sensitive oxidative DNA lesions suppressible by antioxidant cotreatment. Taken together, our data demonstrate that the endogenous AhR ligand FICZ displays nanomolar photodynamic activity representing a molecular mechanism of UVA-induced photooxidative stress potentially operative in human skin.